Ventral tegmental area inactivation alters hormonal, metabolic, and locomotor responses to inescapable stress. (8th August 2019) - Mortazaei, Samaneh; Sahraei, Hedayat; Bahari, Zahra; Meftahi, Gholam Hossein; Pirzad Jahromi, Gila; Hatef, Boshra
Abstract: Context: The involvement of unilateral and bilateral inhibition of the ventral tegmental area (VTA) in response to stress is not well understood. Objective: In the present study, the effect of unilateral and bilateral inhibition of the VTA on hormonal, metabolic, and locomotor responses to stress was assessed. Material and methods: Male rats seven days after cannulation into the VTA received electro foot-shock stress for seven consecutive days. Twenty minutes before induction of stress, 2% lidocaine hydrochloride or sterile saline (control) was injected either uni- or bi-laterally into the VTA. Results: Results showed that stress significantly increased serum corticosterone level, adrenal gland weight and anorexia, reduced weight gain, food-intake, and locomotor activity. However, bilateral inactivation of VTA prevented stress-induced these parameters changes. Conclusion: The present study demonstrated that the bilateral VTA blockade effectively relieves the symptoms of stress, while the unilateral VTA blockade does not significantly improve the changes caused by stress.